Prevalence of Theileria in cattle in China: A systematic review and meta-analysis. (January 2022) - Chen, Yu; Chen, Ying-Yu; Liu, Gang; Lyu, Chuang; Hu, Yang; An, Qi; Qiu, Hong-Yu; Zhao, Quan; Wang, Chun-Ren
Abstract: Theileria, one of the causative agents of blood protozoan, has brought a huge economic loss to the cattle industry worldwide. However, the epidemiology of Theileria in Chinese cattle has not been systematically investigated. This comprehensive review aimed at investigating the prevalence of Theileria infection in cattle in China. A total of 48 published papers on Theileria infection in cattle in China (including data from 21, 366 animals) from inception to October 8, 2021 met the inclusion standard after searching in five databases (Technology Periodical Database, Wan Fang Database, China National Knowledge Infrastructure, PubMed, and ScienceDirect). The pooled prevalence of Theileria in cattle in China was 32.4% identified by using a random effects model. The prevalence in Northeastern China (45.3%) was higher than that in other regions. In the sex subgroup, the prevalence of Theileria was higher in females (48.9%) than that in males (45.8%). The prevalence of Theileria was higher in cattle of free range (34.4%) compared with that of intensive farming (22.3%). The prevalence prior to 2013 (36.1%) was higher than that after 2013 (33.6%). Among three cattle species, dairy cows had the lowest prevalence (21.5%). The prevalence of Theileria ( T. ) annulata (22.2%) and T. sergenti (26.2%) was higher than other species of Theileria ( T. buffeli : 17.5%, T. luwenshuni : 0.9%, T. orientalis : 15.5%, T. ovis : 0.21%, T. sinensis : 20.2%, T. uilenbergi : 6.2%, Others: 0.9%). We also analyzed the impact of different geographic factor subgroups (longitude, latitude, precipitation, temperature, humidity, and altitude) on the prevalence of Theileria in cattle. Among them, climatic factors of longitude, latitude, precipitation, humidity, temperature were associated with the prevalence of Theileria . These analyses suggested that Theileria was common in cattle in China. Targeted prevention programs based on geographic and climatic conditions in different areas may play an important role in reducing Theileria infection among cattle. Highlights: This is the first meta-analysis of the prevalence of Theileria in cattle in China. Theileriosis was common and unevenly varied in Chinese cattle, detection tests, species of Theileria had significant effects. High temperature, heavy rainfall and humidity may be the key points for controlling the spread of Theileria.